Measurement and reduction of the environmental impact of industrial photochemical machining - Ler, Leong Tat (Cranfield University, 1998)
This thesis concerns research into the environmental aspects of the photochemical machining (PCM) industry, involving measurement, analysis, benchmarking, and reducing adverse environmental impacts. The environmental audit of a PCM company found that the likely significant environmental impacts are the use of ferric chloride etchant, solvents and water. A comparison of the environmental performance of two UK PCM companies showed that there were big contrasts in etchant utilisation and solvent and water consumption, indicating that steps could be taken to reduce these impacts. A study to assess the feasibility of using laser direct imaging (LDI), a cleaner technology in photoresist imaging, found that LDI could meet the technical requirements of the PCM industry. For LDI to be economically feasible, the reliability has to be high and maintenance cost has to be low. Audit surveys of PCM companies world-wide regarding etchant utilisation and solvent consumption indicated that: (1) There is a vast difference between the performance of companies and companies that regenerate etchants were more efficient in their FeCl3 utilisation. The industrial best practice for FeCl3 utilisation is 837%. (2) Chlorination was the most popular regeneration method but most companies would use a more environment-friendly system at a higher overall cost. Regarding waste disposal, most companies sent liquid waste etchant for reclaim or recycle. (3) Half of the PCM companies no longer use solvents, and with the development of liquid aqueous-based resists, it is envisaged that PCM practitioners could eliminate the use of solvents in the near future. Lastly, an investigation into the feasibility of using oxygen gas in regenerating FeCI3 showed that the regenerated etchant could produce good quality etchings. This syst'm is also the second cheapest. Therefore, it is a good option for the PCM companies as the cost of regeneration is not too expensive and it is environment-friendly.